An investigation of potential induced degradation of solar photo-voltaic modules under Malaysian climate condition / Md. Aminul Islam - Md. Aminul , Islam (2018)
Photovoltaic (PV) modules experience unanticipated decline in lifespan due to high voltage stress (HVS) of large PV string recognized as potential induced degradation (PID). Real-time data on PID behaviour of PV module under the climate conditions of Malaysia is necessary to estimate the operating capacity of a PV plant which far deviates from the installed capacity after several years of aging. On-site degradation characteristics of PV module under the typical Malaysian climatic condition have been investigated. A quantitative characterization method of PV modules degradation by using electroluminescence (EL) imaging technique has been introduced in this research. About 42% degradation of PV module has been noticed due to nine years field aging under a negative voltage stress produced from 240 V string, whereas during the same period the PV module degrades about 17% over as a consequence of light induced degradation (LID). Shunt resistance of negative end PV module is found 75% lower than that of the positive end module. PV cell crack initiation is observed to be accelerated as a result of cyclic high voltage stress at on-site. The LID characteristics of different poly and monocrystalline silicon PV modules due to real field aging for various time spans have been measured by EL imaging along with the measurement of maximum power and analysis of dark I-V curve. Degradation values of PV modules obtained are 1.78, 7.06, 13.92, 17.04 and 17.42% due to aging for a period of 8 months, 16 months, 4 years, 9 years and 11 years respectively. This degradation is due to the reduction in shunt resistance which declines gradually as a result of aging. PID of PV module depends on the leakage current characteristics. Effect of various operating parameters for example PV module temperature, wet surface condition, dust and salt deposition on module surface and aging on leakage current behaviour are investigated by applying high DC voltage stresses in laboratory condition. Dust particles collected from the PV plant site are characterized by means of field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) spectroscopy and X-ray diffraction (XRD) techniques. It has been observed that, the leakage current increases with the increase of voltage stress at room temperature. An increase of module surface temperature causes a moderate increase of leakage current, but the rising trend is drastic in the presence of water film on module surface. Leakage current values under 1500 V stress are found 7.8, 8.9 and 29.8 μA at 25°C (dry), 60°C (dry) and 45°C (wet) conditions, respectively. The leakage current increases linearly as a consequence of increase in salt existence. Slight amount (2gm/m2) of dust along with water film is found sufficient to trigger leakage current generation in PV module. Tiny dust particles as observed from FESEM are found to attain charged state and can easily attach with ionic compounds that exist in coastal areas, which further instigate the leakage current flow in PV module. Aging of the PV module causes dwindle in leakage current as well as PID resistance property of PV modules resulting from the decline of encapsulant electrical resistance.